Association Between Systemic Immune-Inflammation Index and Stress Urinary Incontinence in Adult Women: A Population-Based Study - Jiang M; Yao X; Jiang H (International Journal of Women's Health)
Mei Jiang,* Xiaodie Yao,* Hua Jiang Department of Gynecology and Obstetrics, Women’s Hospital of Nanjing Medical University, Nanjing Women and Children’s Healthcare Hospital, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua Jiang, Women’s Hospital of Nanjing Medical University, Nanjing Women and Children’s Healthcare Hospital, Nanjing, Jiangsu, 210004, People’s Republic of China, Email jianghua@njmu.edu.cnBackground: Systemic immune-inflammation index (SII) is a novel inflammatory marker, and inflammation may contribute significantly to the aetiology of stress urinary incontinence (SUI), in addition to recognized factors. This study aims to explore the association between SII and SUI in women.Methods: Adult participants from the 2007– 2018 NHANES were included. Weighted multivariate logistic regression and subgroup analysis were conducted to determine the relationship between SII and SUI. The non-linear relationship between SII and SUI risk was evaluated using restricted cubic splines (RCS), and the inflection point was determined by two-piecewise logistic regression.Results: A total of 10,776 women were included, of whom 4407 (40.9%) had SUI. After adjusting for all confounders, a significant positive association between SII and SUI risk was observed (OR: 1.09; 95% CI: 1.01– 1.19, P = 0.021); Moreover, when compared with the women in the lowest SII tertile, those in the highest SII tertile had a 15% increased risk of SUI (OR: 1.15; 95% CI: 1.00– 1.31, P = 0.049). Subgroup analysis showed that there were consistent relationships between SII and SUI across most subgroups. A non-linear relationship between log2SII and SUI was observed by RCS analysis. Furthermore, the two-piecewise logistic regression demonstrated that the odds of being SUI increased with the SII level, and this rising trend gradually slowed down after passing the inflection point of 8.64.Conclusion: Our findings suggest an association between elevated SII levels and an increased likelihood of SUI in women. Further well-designed prospective studies are needed to substantiate our results.Keywords: systemic immune-inflammation index, stress urinary incontinence, population-based study, NHANES, cross-sectional study